Impact of different soil amendments on crude oil polluted soil and performance of maize - Okafor , M.J.; Chidozie , E.I. (AgroChemistry and Soil Science, 2016)
Effects of different soil amendments on crude oil polluted soil and performance of maize was carried out in Egbema, Imo State. The experiment was laid out in a complete randomized design in three replications in pots. Eighteen pots were used in this study, with 9kg soil packed in each pot. The soil in each of the pots was polluted with 22.5g (5t/ha) of crude oil, simulating the spill in the field except in control (Zero pollution). There were six treatments consisting of NPK 20:10:10, Crushed limestone (CaCO3), Cured cow dung (CD), Cured poultry manure (PM), each applied at the same rate of 13.5g (3t/ha) except in control (Ct) and unamended polluted (UP). Percentage organic carbon was determined three times after amendment. Two maize seeds (Oba II) were planted in each pot. Seed emergence, plant height, time of tasseling, time of silking and yield were recorded in this study. The soil was loamy sand; percentage porosity was moderately high across the pots. The texture was not affected by crude oil pollution; however, it influenced the chemical properties of the soil. Percentage organic carbon was high after pollution, pH was reduced and C/N ratio widened. LSD at 5% probability, showed that crude oil pollution affects basic cations in the soil especially magnesium. The amendment however, reduced the percentage organic carbon, narrowed the C/N ratio, and increased the basic cations and the pH. The performance of maize crop in this study showed the positive impact of the amendment materials used on crude oil-polluted soil when compared with control and unamended polluted pots. NPK-treatment showed a high level of amendment than other treatments; with yield 47t/ha for NPK, 24t/ha for Limestone, 20t/ha for Cow dung, 29t/ha for Poultry manure, then 20t/ha and 18t/ha for Control and Unamended polluted.